Antimicrobial susceptibility of coagulase negative Staphylococci isolates from suspected cases of bovine subclinical mastitis in parts of Bundelkhand region - Balendra Singh; Ramesh Kumar (Asian Pacific Journal of Health Sciences, 2018)
Background: Increasing importance of Coagulase negative Staphylococci as etiological agent in health concerns of domestic animals is recognized in various studies. A significant concern of CoNS isolates from bovine subclinical mastitis is development of resistance towards antimicrobials routinely used in management diseases like mastitis. Isolates from study area had not been worked out properly in previous reports. Methodology: 125 Staphylococci sp. isolates identified in previous study by the authors were screened for resistance against 9 antimicrobials of common use using the Kirby Bauer disk diffusion method. Minimal inhibitory concentrations of 8 antibiotics were measured by using EzyTM Strips supplied by Himedia. Multiple drug resistance was also determined by analyzing results with individual antimicrobial agent. Results: Significant resistance towards β-lactam group of antibiotics penicillin and oxacillin was observed in isolates with 85.6 and 41.40 % respectively. Trimethoprim was second group of antibiotics for which isolates were found resistant with 81.60%. 20.8, 12, 10.40, 8.80, and 3.20% isolates were found resistant to erythomycin, tetracyclin, gentamycin, ciprofloxacin and ofloxacin respectively. Thus highest susceptibility was observed to fluoroquinolones. Data analysis also revealed multiple drug resistance in isolates as 44% of isolates was also found resistant to 3 or more antibiotics. On regional basis highest number of antibiotic resistant CoNS isolates was reported from Jhansi followed by Lalitpur and Jalaun. Conclusion: The study revealed the incidence of multiple antibiotic resistances in Coagulase negative Staphylococci isolates from possible cases of bovine subclinical mastitis and if not managed properly may be responsible for horizontal transfer of resistance from animal to man through food born infections.